Oral rehydration salts: a simple and appropriate tool against dehydration due to diarrhoea - Sunoto Sunoto (Paediatrica Indonesiana, 1981)
In spite of the many advances made in diagnosis, pathogenesis and pathophysiology of diarrhoeal diseases, however it is still one of the major public health problems with high morbidity and mortality particularly in children below 5 years of age.Oral Rehydration Therapy (ORT) had been known since the 1950's but the extensive use of ORT in hospitals and treatment centres was just in the 1960's and so it had become a world-wide program since the 1970's.Nowadays more than 70 countries have used ORT as main treatment of dehydration due to diarrhoea. One of the problems of ORT being still in dispute is the Na concentration in ORS. The other extended usee of ORT is the use of sucrose electrolyte solution and sugar-salt solution by using pinch or scoops.It has been proven that ORT has a beneficial impact on improving nutrition state, saving money (economy), and dramatically decreasing mortality due to diarrhoea.National efforts to implement ORT must be part of the general program for delivery of all basic health services. It should be integrated through primary health care such as family planning, nutritional program, MCH, immunization, environmental sanitation, health education, etc.Public campaign using mass media and advertisements plays a great role too in making success of ORT.